Specific antigens in malignancy-associated membranous nephropathy - Hu, Xiaoying; Wang, Guoqin; Cheng, Hong (Frontiers in Medicine, 2024)
Membranous nephropathy (MN) is a glomerular disease mediated by autoimmune complex deposition, with approximately 30% of cases attributed to secondary causes. Among them, malignant tumors are a significant cause of secondary MN. Recent advancements in the identification of MN-specific antigens, such as THSD7A and NELL-1, suggest a potential association with malignant tumors, yet definitive proof of this relationship remains elusive. Therefore, this article aims to review the distribution of MN-specific antigens in patients with MN caused by malignant tumors and the possible role of these antigens in the pathogenesis of the disease.